1981
DOI: 10.1038/bjc.1981.248
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood tumours in Queensland

Abstract: Summary.-The incidence of childhood cancer in Queensland has been studied using the data of the population-based Queensland Childhood Malignancy Registry. During the 7-year period [1973][1974][1975][1976][1977][1978][1979]454 cases were registered, giving an annual agespecific incidence of 11 34/105 for the age group 0-14 years inclusive. There was a male/female ratio of 1-36. The commonest group of diseases was that of the leukaemias, followed by that of CNS tumours. The incidences of the various types of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…In previous studies a predominance of ALL in boys is found (Birch et al, 1980;Ericsson et al, 1978;McWhirter & Bacon, 1981;Teppo et al, 1975;Young & Miller, 1975). According to this finding the male/female ratio for ALL is 1.2 in the Netherlands.…”
Section: Sexmentioning
confidence: 61%
“…In previous studies a predominance of ALL in boys is found (Birch et al, 1980;Ericsson et al, 1978;McWhirter & Bacon, 1981;Teppo et al, 1975;Young & Miller, 1975). According to this finding the male/female ratio for ALL is 1.2 in the Netherlands.…”
Section: Sexmentioning
confidence: 61%
“…The incidences of ALL in each of the 12 areas in Queensland was compar9d with some demographic factors for eacK of these areas (Table II (Congalton, 1969) (Barlow et al, 1972). In an unselected series of 209 other childhood malignancies, mainly solid tumours, from the same period (McWhirter & Bacon, 1981) there was no significant difference in the distribution of the social class of the fathers compared with that of the employed male population.…”
Section: Resultsmentioning
confidence: 99%
“…These should be based on series of cases in children ascertained by incidence rather than by death. Since there may be a difference in survival from leukaemia according to social class (McWhirter et al, 1981;Gibson & Graham, 1974), series which include only patients who have died (Sanders & White, 1981) may contain an excess of children from lower social classes. A case-control study in Queensland is being planned to attempt to define more accurately the factors which influence the incidence of childhood ALL in this state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on cases was obtained from the Queensland Childhood Malignancy Registry (McWhirter & Bacon, 1981). This is a population based registry which includes all children with malignant tumours and also all intracranial tumours who were under the age of 15 years and resident in Queensland at the date of incidence.…”
Section: Methodsmentioning
confidence: 99%